The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1029/rg021i002p00474
|View full text |Cite
|
Sign up to set email alerts
|

Plasma waves in planetary magnetospheres

Abstract: The studies of magnetospheric plasma waves in the 1979–1982 quadrennium have included not only intensive studies of plasma waves in the Earth's magnetosphere but also, for the first time, in situ observations and detailed analyses of plasma waves in the magnetospheres of Jupiter and Saturn. While much of the research has involved the continuing identification and classification of plasma wave phenomena in the magnetospheres, increasingly greater emphasis has been placed on understanding the sources of the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 466 publications
0
5
0
Order By: Relevance
“…Observations of these waves in the magnetosphere of the Earth and their role in the dynamics of the magnetospheric plasma were discussed by many authors (see, e.g., Sazhin, 1982;Carpenter, 1988;Helliwell, 1988). These waves have also been observed in the magnetospheres of other planets (Anderson, 1983;Scarf et al, 1987).…”
Section: Introductionmentioning
confidence: 71%
“…Observations of these waves in the magnetosphere of the Earth and their role in the dynamics of the magnetospheric plasma were discussed by many authors (see, e.g., Sazhin, 1982;Carpenter, 1988;Helliwell, 1988). These waves have also been observed in the magnetospheres of other planets (Anderson, 1983;Scarf et al, 1987).…”
Section: Introductionmentioning
confidence: 71%
“…For a review of past plasma wave phenomena observed in the magnetosphere, see Shawhan [1979a;1979b), Anderson [1983;1984), Inan [1987), and Kurth [1991). In order to distinguish electromagnetic waves from electrostatic waves, the instrumentation included a search coil magnetometer in addition to inputs from the two electric field antenna srtems.…”
Section: Expected Observations and Design Criteriamentioning
confidence: 99%
“…This electrostatic noise is also observed along these field lines to low altitudes over the discrete aurora (Gurnett and Frank, 1977). On the other hand, these plasma waves are relatively absent in the plasma sheet, including the current sheet centered on the neutral sheet (Anderson, 1983). Various mechanisms are proposed to account for the presence of broadband electrostatic noise (Huba et al, 1978;Grabbe and Eastman, 1984), none of which are completely successful.…”
Section: The Plasma Sheet and Its Boundary Layermentioning
confidence: 99%